Mechanical ventilation induces brainstem inflammation in preterm fetal sheep - Vidinopoulos, Kayla; Azman, Zahrah; Somers, Ainsley; Zahra, Valerie A.; Thiel, Alison; Lu, Hui; Pham, Yen; Tran, Nhi Thao; Allison, Beth J.; Herlenius, Eric; Hooper, Stuart; Galinsky, Robert; et al. (Frontiers in Pediatrics, 2023)
Background: Preterm infants have immature respiratory drive and often require prolonged periods of mechanical ventilation. Prolonged mechanical ventilation induces systemic inflammation resulting in ventilation-induced brain injury, however its effect on brainstem respiratory centers is unknown. We aimed to determine the effects of 24 hours of mechanical ventilation on inflammation and injury in brainstem respiratory centres of preterm fetal sheep.Preterm fetal sheep at 110 ± 1 days (d) gestation were instrumented to provide mechanical ventilation in utero. At 112 ± 1 d gestation, fetuses received either mechanical ventilation (VENT; n=7; 3 ml/kg) for 24 h, or no ventilation (CONT; n=6). At post-mortem, fetal brainstems were collected for assessment of mRNA and histological markers of inflammation and injury.In utero ventilation (IUV) did not alter any blood-gas parameters. IUV significantly increased systemic IL-6 and IL-8 concentrations over the 24h period compared to CONT. The number of ameboid microglia within the nucleus tractus solitarius and the raphe nucleus increased in VENT fetuses (p<0.05 for both vs. control). The % area fraction of GFAP+ staining was not significantly higher within the preB𝑜ẗzinger complex (p=0.067) and retrotrapezoid nucleus and parafacial respiratory group (p=0.057) in VENT fetuses compared to CONT. Numbers of caspase-3 and TUNEL-positive cells were similar between groups.Gene expression (mRNA) levels of inflammation, injury, cell death and prostaglandin synthesis within the brainstem were similar between groups.Mechanical ventilation induces a systemic inflammatory response with only moderate inflammatory effects within the brainstem respiratory centres of preterm fetal sheep.